Development of an aeration system for use in plant tissue 9 - Lee, R; Ratcliffe, R (1983)
An experimental arrangement is described that enables 31P nuclear magnetic resonance (NMR) spectra of plant tissue to be recorded while circulating a medium over the sample. The system makes it possible to prevent anoxia developing in the NMR tube, and this increases the potential of the NMR technique. © 1983 Oxford University Press.